Exploring the relationship between cathepsin and age-related macular degeneration using Mendelian randomization - Wang, Qiuyuan; Cai, Shanjun (Frontiers in Medicine, 2024)
Purpose: Age-related macular degeneration (AMD) is the main cause of low vision and even blindness in the elderly population worldwide. However, no study has been conducted to analyse the causal relationship between cathepsin family and AMD. The present study explored and analysed the potential association via Mendelian randomisation (MR).Methods: In this study, AMD was classified as exudative AMD and atrophic AMD. Inverse variance weighted (IVW) was used as the main analysis method. The association between nine cathepsins and two AMD classifications was analysed using Multivariable Mendelian randomization(MVMR). Sensitivity analysis included Cochran's Q-test and MR-Egger intercept test.Results: Univariate MR analysis showed that high levels of cathepsin L2 could delay the development of atrophic AMD (IVW: P = 0.017; OR = 0.885; 95% CI = 0.799-0.979). Reverse MR analysis indicated that cathepsin E increased in the occurrence of atrophic (IVW: P = 0.023; OR = 1.058; 95% CI = 1.007-1.111) and exudative AMD (IVW: P = 0.018; OR = 1.061; 95% CI 1 = 1.010-1.115). MVMR analysis indicated a causal relationship between cathepsin G (IVW: P = 0.025; OR = 1.124; 95% CI = 1.014-1.245), cathepsin O (IVW: P = 0.043, OR = 1.158,95% CI = 1.004-1.336) and exudative AMD after the coordination of other types of cathepsin.Conclusion: This study demonstrated a potential link between the cathepsin fa mily and the onset of AMD, where the elevated serum cathepsin L2 concentration may be a protective factor for atrophic AMD, and the elevated serum cathepsin G, O concentrations maypromote the development of exudative AMD. However, the d evelopment of AMD may be accompanied by elevated serum cathepsin E concentr ations.